A Novel Heterozygous Intronic Mutation in the FBN1 Gene Contributes to FBN1 RNA Missplicing Events in the Marfan Syndrome. (29th May 2018) - Torrado, Mario; Maneiro, Emilia; Trujillo-Quintero, Juan Pablo; Evangelista, Arturo; Mikhailov, Alexander T.; Monserrat, Lorenzo
Abstract : Marfan syndrome (MFS) is an autosomal dominantly inherited connective tissue disorder, mostly caused by mutations in the fibrillin-1 ( FBN1 ) gene. We, by using targeted next-generation sequence analysis, identified a novel intronic FBN1 mutation (the c.2678-15C>A variant) in a MFS patient with aortic dilatation. The computational predictions showed that the heterozygous c.2678-15C>A intronic variant might influence the splicing process by differentially affecting canonical versus cryptic splice site utilization within intron 22 of the FBN1 gene. RT-PCR and Western blot analyses, using FBN1 minigenes transfected into HeLa and COS-7 cells, revealed that the c.2678-15C>A variant disrupts normal splicing of intron 22 leading to aberrant 13-nt intron 22 inclusion, frameshift, and premature termination codon. Collectively, the results strongly suggest that the c.2678-15C>A variant could lead to haploinsufficiency of the FBN1 functional protein and structural connective tissue fragility in MFS complicated by aorta dilation, a finding that further expands on the genetic basis of aortic pathology.